A study on qualitative comparison between cryostat and conventional technique for histopathology diagnosis - C. Zinzala, Dr. Umeshkumar; P. Goswami, Alpeshpuri; Goswami, Parth; Gondliya, Jignesh; Brahmbhatt, Smit; Khandkar, Abhijeet (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Intraoperative consultation by frozen section technique is an invaluable tool for immediate diagnosis. The correlation of intraoperative frozen section diagnosis with final diagnosis on permanent section is an integral part of quality assurance in surgical pathology. Its accuracy and limitations vary with different anatomical sites. Aims & Objective: Qualitative morphological comparison between frozen section and routine formalin fixed paraffin embedded sections in different tissues, to assess the accuracy of frozen section, to detect the number and type of discrepancies and to assess the causes for discrepancies. Material and Method: The present study retrospectively reviewed frozen sections performed in the pathology department, Sir-t hospital, government medical college, Bhavnagar during a period of 2 year. Diagnostic accuracy of frozen section and its morphological quality and reliability in comparison to histopathology was evaluated by 2 pathologists in a blinded fashion for the following parameters: cellular outline, nuclear and cytoplasmic features, staining pattern and overall morphology. The results were compared to the routine formalin fixed paraffin sections to evaluate diagnostic accuracy. Discordant cases were reassessed to find the reasons for discrepancy. Result: Diagnostic accuracy of frozen section was 95.1% with false negative case are 4.8% and no false positive case. Statistical analysis showed that most common indications of frozen section in the present study was presence/typing of neoplasm (61.2%) followed by assessment of margin (35.6%) and assessment of nodal status (3.2%). It was observed that nuclear details, cellular outline and overall morphological quality of frozen section was slightly inferior to that of routine histopathology section, however, staining and cytoplasmic details were comparable. The discrepancies were mainly due to technical artefacts (9.7%), sampling error (3.2%) interpretation error (1.6%), and partly due to lack of interdepartmental communication. Conclusion: Frozen section diagnosis is very useful and highly accurate procedure. Gross inspection, sampling by pathologist, frozen complemented with cytological and histological review and intimal cooperation with surgeon can avoid certain limitations and provide rapid, reliable, cost effective information necessary for optimum patient care.